Pengembangan Keterampilan Kolaborasi Melalui Penerapan Modul Interaktif Berbasis TTI - Fahmi, Reza; Tusa'diah, Halimah; Aswirna, Prima; Sabri, Ahmad (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
The development of science and technology has had a major influence in all aspects of life, including in the world of education. One way of using technology in learning is the use of technological resources in the learning process such as technology-based interactive modules.The use of modules in learning aims so that students can learn independently without or with guidance from educators, so that students will learn better if they do it alone which focuses directly on mastering learning objectives. The aim of this research is to produceInteractive module based on Trait Treatment Interaction (TTI) using Adobe Flash on collaborationÂ  skills with students on the material of the kinetic theory of gases and the laws of thermodynamics class XI SMA / MA valid, practical and effective. This research is a research and development (R&D). Development design is using a development model ADDIE consists of: the Analysis stage (analyzing), the Design stage (designing), the Development stage (developing), the Implementation stage (implementing) and the Evaluation stage (evaluating). The instruments used in this study were a validity questionnaire, a practicality questionnaire, and an effectiveness test. The product validity test is given by expert validators in the aspects of material / content, media / construction, and language. The practicality test is givenÂ  to educators and students, while the effectiveness test is given to students. The results of the research were produced Interactive module based on Trait Treatment Interaction (TTI) using Adobe Flash for students on the material of the kinetic theory of gases and the laws of thermodynamics which is very valid, very practical and very effective against collaboration skills of students.